A study of marital conflict on measures of social support and mental health - Tam, Cai Lian *; Lim, Siew Geok * (Sunway University College, 2008)
Marital conflict tactics and social supports have been proven to predict health outcomes in couples. The purpose of this study is to examine the effects of marital conflict tactics and social support on the general health of couples in Malaysia. It also aims to find out which type of perceived social support has a greater impact on an individual and his?her spouse?s mental health. A random sample of 399 participants from Selangor who were either married or cohabiting were used in this study. Characteristics of conflict tactics and perceived social support in relation to general health were assessed. The result shows a moderate correlation between the variables. This supports the hypothesis that the manner in which couples handle conflict has an influence on their mental health. Additionally, couples? ability to handle conflict is also related to perceived social support. This means that a person with a better conflict tactic scale and more perceived social support is more likely to have a better general health.